Characterisation of microbial diversity and chemical properties of Cheddar cheese prepared from heat-treated milk. (December 2016) - Lee, Ji Young; Joung, Jae Yeon; Choi, Yun-Sang; Kim, Younghoon; Oh, Nam Su
Abstract: Cheese made with low temperature/long time-treated milk and thermised milk (LC and TC, respectively) showed diverse bacterial community patterns, while cheese made with high temperature/short time-treated milk (HC) showed the lowest microbial diversity. Although the proportion of subdominant species was <1%, significant differences in community patterns were observed. In particular, the proportions of Lactobacillus casei and Lactobacillus delbrueckii in LC and TC were significantly greater than those in HC. Moreover, chemical analysis revealed the highest proteolytic and lipolytic activities in TC. Based on these results, the characteristics of Cheddar cheese were influenced by bacterial communities in low abundance, which were affected by the type of heating applied to the cheese milks. Furthermore, the diversity of these bacterial communities is highly correlated with the heat treatment of milk, and different treatment methods can be used to alter the chemical metabolism of lactose, fat, and protein during ripening.